The Implementation of Multi-Objective Optimization Based on Ratio Analysis Method to Determine KIP Participants - Frainskoy Rio Naibaho (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2020)
Decision Support System (DSS) is a system with mathematical calculations that can assist a person in making decisions from various criteria, types, and options[1]. The calculation is done accurately and according to the desired target. Institut Agama Kristen Negeri (IAKN) Tarutung is a state-owned religious higher education institution. In providing education, IAKN Tarutung provides several scholarships for outstanding students with economically disadvantaged students. One of them is the Kartu Indonesia Pintar (KIP)[2]. The purpose of this research is to develop the MOORA method to assist in decision making in determining which participants are eligible for KIP scholarships. Development of the Multi-Objective Optimization Based on Ratio Analysis (MOORA) method is expected to provide the best alternative solutions that are right on target without any personal interest[3].